Clinical outcomes of 3–5 years follow-up of immediate implant placement in posterior teeth: a prospective study - Rusama Wipawin; Parinya Amornsettachai; Woraphong Panyayong; Dinesh Rokaya; Sasipa Thiradilok; Patr Pujarern; Suphachai Suphangul (BMC Oral Health, 2024)
Abstract Background Immediate implant placement in posterior teeth has become popular in recent years. However, only a few studies focused on evaluating the long-term success of immediate implant placement. Purpose To analyze the clinical outcomes of immediate implant placement in the posterior region with conventional loading with 3–5 years follow-up following the International Congress of Oral Implantologists (ICOI) Pisa Consensus Conference. Method The study was done in 25 bone-level implants (Straumann® SLActive® bone level tapered implant, Straumann®, Basel, Switzerland) in 19 patients who underwent immediate implant placement in a posterior tooth with conventional loading with 3–5 years follow-up. The overall success and survival of these placements were evaluated following the International Congress of Oral Implantologists (ICOI) Pisa Consensus Conference using chart records, clinical examination, radiographic evaluation, and outcomes measurement. Patient satisfaction was evaluated by using a numeric rating scale. The biological and technical status, modified Pink Esthetic Score (mPES), complications, and marginal bone change were also evaluated. The analysis was done using SPSS version 21 (SPSS Inc., Chicago, IL, USA). The data were analyzed using a paired samples t-test. Results It was found that 24 out of the 25 (96%) dental implants survived for an average of 57 ± 8.07 months. All of the 24 surviving dental implants were considered an operational success. The average mPES was 9.75 ± 0.44. The major prosthetic complications seen were: (1) proximal contact loss (41.67%), (2) loosening of the screw (8.33%), and (3) cement debonding (4.17%). Conclusions Immediate implant placement in a posterior tooth with conventional loading yields a predictable result with some complications. The most prominent complications were proximal contact loss, followed by loosening of the screw and cement debonding. The implant survival rate was 96% at a mean time follow-up of 4 years and 9 months.